Clinical performance of bulk-fill and conventional resin composite restorations in posterior teeth: a systematic review and meta-analysis - Veloso, Sirley Raiane Mamede; Lemos, Cleidiel Aparecido Araújo [UNESP]; de Moraes, Sandra Lúcia Dantas; Do Egito Vasconcelos, Belmiro Cavalcanti; Pellizzer, Eduardo Piza [UNESP]; de Melo Monteiro, Gabriela Queiroz (Springer Nature, 2018)
Objectives: The purpose of this systematic review was to compare the clinical performance of bulk-fill resin composites with conventional resin composites used for direct restorations of posterior teeth. Methods: This review followed the PRISMA statement. This review was registered at PROSPERO (registration number CRD42016053436). A search of the scientific literature was performed by two independent reviewers using the PubMed/MEDLINE, Embase, The Cochrane Library, and Web of Science databases from commencement until January 2018. The research question was “Do bulk-fill resin composites have a clinical performance comparable to conventional resin composites in posterior restorations?” Only studies evaluating class I and II direct restorations in permanent teeth with a follow-up period of at least 1 year were included. The RevMan 5 program was used for meta-analysis, calculating the relative risk (RR) and 95% confidence interval (CI) of the dichotomous outcome (restoration failure or success). Results: Ten articles were selected, comprising 941 analyzed restorations. The mean follow-up period was 33.6 months (12–72 months). No statistically significant differences in the failure rate were observed between conventional and base/flowable bulk-fill resin composites (p = 0.31; RR 1.49; 95% CI 0.69–3.25) or full-body/sculptable bulk-fill resin composites (p = 0.12; RR 1.89; 95% CI 0.84–4.24). Conclusions: The present systematic review and meta-analysis indicate similar clinical performances of bulk-fill and conventional resin composites over a follow-up period of 12 to 72 months. Clinical significance: Based on the results of this study, the bulk-fill resin composites could be an alternative for direct restorations in posterior teeth. However, clinical trials of longer duration are required.
Keywords: Bulk-fill resin; Dental restoration; Direct restoration; Incremental filling technique; Resin composite; Systematic review